2018
DOI: 10.3389/fpls.2018.01302
|View full text |Cite
|
Sign up to set email alerts
|

Screening Oat Genotypes for Tolerance to Salinity and Alkalinity

Abstract: A set of four experiments was conducted to develop methods for screening oat tolerance to salt and alkali and the following results were obtained. (1) In experiment 1, 68.5 mmol L-1 salt and 22.5 mmol L-1 alkali were identified as appropriate concentrations for determining oat tolerance to salinity and alkalinity during germination. (2) These concentrations were used in experiment 2 to screen 248 oat genotypes and 21 were identified to be tolerant to salinity and alkalinity in germination. (3) In experiment 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…The reductions of physiological and growth responses to salinity in various N treatments were higher for ND than for SA, indicating a greater tolerance to salinity of genotype SA than of ND. Similar results were also reported as screening 262 oat genotypes for tolerance to salinity and alkalinity [18]. Although SA was more salt tolerant than ND, the performance of physiology, growth, and yield of both genotypes to soil salinity enhanced with the increased N rates, as the mechanism for increasing N rates to alleviate salt stress worked in the same mode of action for both genotypes.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The reductions of physiological and growth responses to salinity in various N treatments were higher for ND than for SA, indicating a greater tolerance to salinity of genotype SA than of ND. Similar results were also reported as screening 262 oat genotypes for tolerance to salinity and alkalinity [18]. Although SA was more salt tolerant than ND, the performance of physiology, growth, and yield of both genotypes to soil salinity enhanced with the increased N rates, as the mechanism for increasing N rates to alleviate salt stress worked in the same mode of action for both genotypes.…”
Section: Discussionsupporting
confidence: 81%
“…Understanding the interaction between salinity and N fertilization is of a great agronomic and economic importance for crop production [10,20]. Most studies in salinity and nitrogen have focused either on salinity as a limiting factor for crop growth [16,18] or on the N influence on crop growth [17], while their interactive effects are still not fully understood. In our study, we found that the photosynthetic rate, nitrogen use efficiency, plant height, and grain yield were significantly affected by the interaction of salinity stress and N fertilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkalinity inhibits photosynthesis, stomatal conductance, and transpiration rates more severely than salinity ( Chen et al, 2011 ). Greater limitations on germination rate and yield have been observed under alkali stress than under salt stress in oats ( Bai et al, 2018 ). However, the mechanisms of alkali toxicity are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other crops, oat exhibits marked physiological traits when exposed to salinity, and is therefore useful as a study species in examining the physiological responses of cereal crops to sodic-alkalinity, which is more seriously limiting than salinity to agricultural productivity. However, oat genotypes such as Vao-9, Baiyan5, 16SA120850, 153ND121147, 121OA1432-5, and 5SA120093, also differ in their physiological responses to salinity or sodic-alkalinity [ 22 , 23 ]. Yanke1 and Caoyou1 are two lines of naked oats; Yanke1 is an edible oat line bred from 8115-1-2 and Jian1, and Caoyou1 is a grass oat line bred from 578 and Hebo1.…”
Section: Introductionmentioning
confidence: 99%